Selective episiotomy versus no episiotomy – A clinical study on primigravida - Neogi, Joydip; Chaudhuri, Rahul; Nandi, Swarna; Chowdhury, Ranita Roy; Pal, Manidip (Asian Journal of Medical Sciences, 2021)
Background: Episiotomy is the incision given over the pudendum, i.e. on the external genitalia organ during the vaginal delivery. Aims and Objective: In this study it has been tried to evaluate the benefits and the risks of selective episiotomy over spontaneous lacerations. Materials and Methods: This is an institution based interventional longitudinal study carried out in the Department of Obstetrics & Gynaecology of College Of Medicine & JNM Hospital, Kalyani over a period of 18 months in 218 patients (109 in each group) fulfilling the inclusion criteria. The recruitment and allocation in episiotomy and non-episiotomy groups were random after proper consent from the participants. Results: The frequency of postpartum perineal pain was around 47% in no episiotomy group and around 60% in selective episiotomy group. There were no cases of dehiscence, haematoma or wound infection in either of the groups. Around 96.22% of the women in the non-episiotomy group were satisfied or very satisfied compared to 89.52% in the selective episiotomy group. Conclusion: An episiotomy rate of less than 1% found in no episiotomy group as compared to around 18% episiotomy rate in selective episiotomy group. However, they have almost same feto-maternal outcome which successfully establish the effectiveness of no episiotomy practice over the selective one.